Copper nanoclusters and their application for innovative fluorescent detection strategies: An overview - Mariagrazia Lettieri; Pasquale Palladino; Simona Scarano; Maria Minunni (Sensors and Actuators Reports, 2022)
Nanomaterials have revolutionized the design of the detection strategies, and nowadays nanoparticles are extensively employed in innovative assays for the selective and sensitive detection of a large variety of analytes. Recently, a new nanomaterials category, namely nanoclusters (NCs), is rapidly emerging. These nanostructures offer great advantages in terms of stability and ease of fabrication. The increasing interest in NCs applications, well represented by the wide bibliography reporting on gold and silver NCs, opens new perspectives for copper nanoclusters (CuNCs). Compared to noble metals, CuNCs not only are more easily available and inexpensive, but also display unique photoluminescent properties with large Stokes shifts, low toxicity, and high biocompatibility, providing high sensitivity even in complex biological matrices. In this review, we present some relevant aspects in the application of CuNCs to various detection strategies, reporting the main features that define the most interesting CuNCs properties, focusing on CuNCs as a promising functional nanomaterial for the development of innovative fluorescent-based platforms.